2017
DOI: 10.18203/2349-3291.ijcp20170707
|View full text |Cite
|
Sign up to set email alerts
|

Immunization status of 24-35 months old children in urban slums of Ahmedabad, Gujarat, India: a cross sectional study

Abstract: Background: Immunization is one of the most cost effective methods of preventing childhood diseases and needs to be sustained with higher coverage for desired benefits. Objective of the study was to assess immunization coverage in children of 24-35 months of age group in urban slums of Ahmedabad city, India.Methods: Using the purposive sampling method, a cross sectional community based study was conducted in urban slum area (Vadaj area) of Ahmedabad city during July-November 2014. All 214 children of 24-35 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…This was followed by not being contacted to come for vaccination (7 responses), session time not being convenient (5 responses), no perceived need, no one to take the child for vaccination and fear of adverse events following immunization (3 responses each). 3 Low availability of vaccination card was seen in NFHS 5 Gujarat. As per NFHS 5 Gujarat 76.3% were fully immunized and 75.9% were fully immunized in rural area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by not being contacted to come for vaccination (7 responses), session time not being convenient (5 responses), no perceived need, no one to take the child for vaccination and fear of adverse events following immunization (3 responses each). 3 Low availability of vaccination card was seen in NFHS 5 Gujarat. As per NFHS 5 Gujarat 76.3% were fully immunized and 75.9% were fully immunized in rural area.…”
Section: Resultsmentioning
confidence: 99%
“…The current scenario depicts that immunization coverage has been steadily increasing but the average level remains far less than the desired. 3 The recent national family health survey-V (NFHS-V) data shows that immunization coverage has been steadily increasing but the average level remains far less than the desired. Still only 76.3% and 76.4% of the infants in Gujarat and India respectively are fully immunized which is less than the desired goal of achieving 85 per cent coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Pentavalent 3 vaccine was taken by 82% and Measles vaccine by 84% of the children. Thakor et al [21] in his study in Ahmedabad, Gujurat showed that vaccination coverage was maximum for BCG (96.7%) followed by pentavalent first dose (95.8%), whereas Panda et al, in a study done in urban slums of Odisha, found that BCG coverage was 96% followed by DTP3 (92%) [11].…”
Section: Discussionmentioning
confidence: 97%